Pengaruh Harga, Label Halal, Kualitas Produk Terhadap Keputusan Pembelian Produk Herbal Hni-Hpai (Studi Kasus Pada Stokis Center Hni-Hpai Dusun Kanigoro, Desa Puton, Diwek, Jombang) - Rizki Putri Utami; Winaika Irawati (Prodi Manajemen Fakultas Ekonomi Universitas Hasyim Asy'ari Tebuireng Jombang, 2022)
The research concerning the influence of price, halal label, and product quality on a purchasing decisionsfor Hni-Hpai’s herbal product Kanigoro Hamlet, Puton Village, Diek, Jombang aimed to discover the influence of one variable on another. Using a multiple linear analysis supported by qualitative analysis. The approach used in this study was quantitative using a saturated sampling technique with a total of 80 people. The result of the study showed that (1)there was an influence of a price on a purchasing decisions for Hni-Hpai products, Hamlet Kanigoro, Puton Village, Diwek, Jombang which could be seen from the t-test of 2.380 with a significant value of 0.020 (2) Halal Label on product’s purchasing decisions Hni-Hpai Kanigoro Hamlet, Puton Village, Diwek, Jombang was 2.134 with a significant 0.036 (3) Produk Quality on a purchasing decisions Hni-Hpai product Kanigoro Hamlet, Puton Village, Diwek, Jombangwa 6.256 with a significant 0.000 (4) Price, halal label, product quality simultaneously influenced the purchasing decision which was 120.628. Keywords: Price; Halal Label; Product Quality; Purchasing Decisions